Albuminuria, Reduced Kidney Function, and the Risk of ST‐ and non–ST‐segment–elevation myocardial infarction. Issue 20 (16th October 2018) - de Chickera, Sonali N.; Bota, Sarah E.; Kuwornu, John Paul; Wijeysundera, Harindra C.; Molnar, Amber O.; Lam, Ngan N.; Silver, Samuel A.; Clark, Edward G.; Sood, Manish M.
Abstract : Background: Chronic kidney disease is a recognized independent risk factor for cardiovascular disease, but whether the risks of ST‐segment–elevation myocardial infarction (STEMI) and non–ST‐segment–elevation myocardial infarction (NSTEMI) differ in the chronic kidney disease population is unknown. Methods and Results: Using administrative data from Ontario, Canada, we examined patients ≥66 years of age with an outpatient estimated glomerular filtration rate (eGFR) and albuminuria measure for incident myocardial infarction from 2002 to 2015. Adjusted Fine and Gray subdistribution hazard models accounting for the competing risk of death were used. In 248 438 patients with 1.2 million person‐years of follow‐up, STEMI, NSTEMI, and death occurred in 1436 (0.58%), 4431 (1.78%), and 30 015 (12.08%) patients, respectively. The highest level of albumin‐to‐creatinine ratio (>30 mg/mmol) was associated with a 2‐fold higher adjusted risk of both STEMI and NSTEMI among patients with eGFR≥60 mL/(min·1.73 m 2 ) compared to albumin‐to‐creatinine ratio <3 mg/mmol. The lowest level of eGFR (<30 mL/[min·1.73 m 2 ]) was not associated with higher STEMI risk but with a 4‐fold higher risk of NSTEMI compared to those with eGFR≥60 mL/(min·1.73 m 2 ). The lowest eGFR (<30 mL/[min·1.73 m 2 ]) and highest albumin‐to‐creatinine ratio (>30 mg/mmol) were associated with a greater than 4‐fold higher risk of both STEMI and NSTEMI (subdistribution hazard models [95% confidence interval] 4.53 [3.30‐6.21] and 4.42 [3.67‐5.32], respectively) compared to albumin‐to‐creatinine ratio <3 mg/mmol and eGFR≥60 mL/(min·1.73 m 2 ). Conclusions: Elevations in albuminuria are associated with a higher risk of both NSTEMI and STEMI, regardless of kidney function, whereas reduced kidney function alone is associated with a higher NSTEMI risk.